A tensile fire-resistant insulated cable and its preparation process
By using high-density polyethylene, polypropylene and other materials in the cable, a cable with excellent tensile and refractory properties is prepared, which solves the problem of flammability of traditional cables in high temperature environments and ensures the safety and reliability of the cables in complex environments.
Patent Information
- Application Number
- CN202411233883.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Traditional cables are prone to softening and burning in high-temperature environments, resulting in cable failure and even causing safety accidents such as fires. They cannot meet the tensile, fire resistance and insulation performance requirements of special occasions such as high-rise buildings, subways, nuclear power plants, etc.
A tensile refractory insulated cable is adopted, which includes a copper wire core wire and a tensile refractory insulated jacket outside the copper wire core wire. The jacket is composed of high-density polyethylene, polypropylene, refractory reinforcer, reinforced glass fiber, titanium dioxide, silicon micropowder and other materials, and is prepared through a specific process to form excellent tensile and refractory properties.
It significantly improves the tensile and fire resistance of the cable, can maintain the mechanical strength and electrical performance of the cable in high temperature environments, ensures the safety and reliability of the cable in emergency situations such as fires, and meets the needs of use in complex environments.
Smart Images

Figure BDA0005027136220000161
Abstract
Description
Technical Field
[0001] The invention relates to the field of cables, and in particular to a tensile-resistant fire-resistant insulated cable and a preparation process thereof. Background Art
[0002] Cable is a kind of wire and cable product used to transmit electric energy, signals and data, usually composed of conductor, insulation layer and sheath. With the rapid development of the power industry, the application field of cables is becoming more and more extensive, and the performance requirements of cables are becoming higher and higher. In some special occasions, such as high-rise buildings, subways, nuclear power plants, etc., cables need to have tensile strength, fire resistance, insulation and other properties to ensure safe operation in emergency situations such as fire.
[0003] However, traditional cable materials are prone to softening and burning in high temperature environments, leading to cable failure and even fire accidents. Therefore, it is of great practical significance to develop a cable with excellent tensile strength and fire resistance. Summary of the invention
[0004] In order to overcome the above technical problems, the purpose of the present invention is to provide a tensile-resistant and fire-resistant insulated cable and its preparation process, which solves the problem that traditional cables have certain limitations in tensile performance and fire resistance and cannot meet the needs of special occasions.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A tensile-resistant fire-resistant insulated cable, comprising a copper wire core and a tensile-resistant fire-resistant insulating jacket outside the copper wire core;
[0007] Wherein, the tensile fire-resistant insulating jacket comprises the following components in parts by weight:
[0008] 56-68 parts of high-density polyethylene, 13-19 parts of polypropylene, 7-15 parts of fire-resistant reinforcing agent, 3-11 parts of reinforcing glass fiber, 4-8 parts of titanium dioxide, 3.5-6.5 parts of silicon powder, 1-3 parts of calcium stearate, 0.9-1.5 parts of polyethylene wax, 0.5-1.1 parts of antioxidant 1010 and 0.3-0.7 parts of compatibilizer ABS-g-MAH.
[0009] As a further solution of the present invention: the fire-resistant reinforcing agent is prepared by the following steps:
[0010] Step a1: 4-formylphenylboronic acid, melamine and anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20-25° C. and a stirring rate of 300-400 r / min for 20-30 min, and then the temperature is raised to 80-90° C. and stirred for reaction for 2-3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain intermediate 1;
[0011] Step a2: Add intermediate 1, DOPO and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction for 15-20 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then raise the temperature to 80-90°C and continue stirring the reaction for 8-10 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then placed in a vacuum drying oven and dried at a temperature of 60-65°C for 6-8 hours to obtain a fire-resistant enhancer.
[0012] As a further solution of the present invention: the usage ratio of the 4-formylphenylboric acid, melamine and anhydrous ethanol in step a1 is 30 mmol:10 mmol:40-50 mL.
[0013] As a further solution of the present invention: the usage ratio of the intermediate 1, DOPO and anhydrous ethanol in step a2 is 10 mmol:30 mmol:50-60 mL.
[0014] As a further solution of the present invention: the reinforced glass fiber is prepared by the following steps:
[0015] Step b1: add phosphorus oxychloride, triethylamine and ethyl acetate to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, stir and react for 30-40 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then add eugenol solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the addition is completed, the temperature is raised to 25-30°C and the stirring reaction is continued for 15-20 hours. After the reaction is completed, add the reaction product to ice water, then stand and stratify, dry the organic phase with anhydrous magnesium sulfate, and then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain intermediate 2;
[0016] Step b2: adding m-chloroperbenzoic acid and ethyl acetate to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, stirring the reaction for 30-40 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then adding the intermediate 2 solution dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and continuing to stir the reaction for 15-20 hours under the condition of heating to 45-50°C after the dropwise addition is completed. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with saturated sodium bicarbonate solution, saturated brine and distilled water for 2-3 times in sequence, and then allowed to stand for stratification, the organic phase is dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain intermediate 3;
[0017] Step b3: Add intermediate 3, silane coupling agent KH550, aluminum phosphotungstate and anhydrous acetone to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then heat to 50-55°C and stir and react for 3-5 hours. After the reaction is completed, cool the reaction product to room temperature, then remove the solvent by rotary evaporation to obtain a fiber modifier;
[0018] Step b4: Add glass fiber, fiber modifier and ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stir and react for 20-30 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then raise the temperature to reflux and continue stirring and reacting for 8-10 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with anhydrous ethanol for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 4-5 hours to obtain reinforced glass fiber.
[0019] As a further solution of the present invention: the dosage ratio of the phosphorus oxychloride, triethylamine, ethyl acetate and eugenol solution in step b1 is 10 mmol: 33-35 mmol: 50-60 mL: 33-35 mL.
[0020] As a further solution of the present invention: the eugenol solution in step b1 is a solution formed by dissolving eugenol in ethyl acetate at a ratio of 10 mmol:10 mL.
[0021] As a further solution of the present invention: the usage ratio of the meta-chloroperbenzoic acid, ethyl acetate and intermediate 2 solution in step b2 is 33-36 mmol: 70-80 mL: 30 mL.
[0022] As a further solution of the present invention: the intermediate 2 solution in step b2 is a solution formed by dissolving the intermediate 2 in ethyl acetate at a ratio of 10 mmol:30 mL.
[0023] As a further solution of the present invention: the usage ratio of the intermediate 3, silane coupling agent KH550, aluminum phosphotungstate and anhydrous acetone in step b3 is 10 mmol: 33-36 mmol: 0.8-1.6 g: 80-100 mL.
[0024] As a further solution of the present invention: the usage ratio of the glass fiber, the fiber modifier and the ethanol solution in step b4 is 10g:1.2-5.8g:100-120mL.
[0025] As a further solution of the present invention: the glass fiber in step b4 is ECS 301T glass fiber, and the volume fraction of the ethanol solution is 75-85%.
[0026] As a further solution of the present invention: a preparation process of a tensile fire-resistant insulated cable comprises the following steps:
[0027] Step 1: Weigh 56-68 parts of high-density polyethylene, 13-19 parts of polypropylene, 7-15 parts of fire-resistant enhancer, 3-11 parts of reinforcing glass fiber, 4-8 parts of titanium dioxide, 3.5-6.5 parts of silicon powder, 1-3 parts of calcium stearate, 0.9-1.5 parts of polyethylene wax, 0.5-1.1 parts of antioxidant 1010 and 0.3-0.7 parts of compatibilizer ABS-g-MAH according to weight parts;
[0028] Step 2: Add high-density polyethylene, polypropylene, fire-resistant reinforcing agent, reinforcing glass fiber, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mix evenly to obtain a mixture;
[0029] Step 3: Add the mixture into the extruder, melt and extrude it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket to obtain a tensile-resistant and fire-resistant insulating cable.
[0030] Beneficial effects of the present invention:
[0031] A tensile fire-resistant insulated cable and its preparation process of the present invention are as follows: high-density polyethylene, polypropylene, fire-resistant reinforcing agent, reinforced glass fiber, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH are added to a mixer and mixed evenly to obtain a mixture, and the mixture is added to an extruder and melt-extruded to the outside of the copper wire core to form a tensile fire-resistant insulating jacket to obtain a tensile fire-resistant insulated cable; the preparation process significantly improves the tensile performance and fire resistance of the cable by optimizing the material formula, can improve the mechanical strength and electrical performance of the cable, can ensure the safety and reliability of the cable during long-term use, can also maintain the integrity and electrical performance of the cable in emergency situations such as fire, and meet the use requirements in complex environments. At the same time, the preparation process is simple, the material cost is low, and it has a wide range of application prospects. In the fields of electricity, communication, transportation, etc., it can replace traditional cable materials and improve the safety and reliability of the cable.
[0032] In the process of preparing the tensile fire-resistant insulated cable, a fire-resistant enhancer is first prepared, and 4-formylphenylboronic acid and melamine are reacted, and the formyl group on the 4-formylphenylboronic acid reacts with the amino group on the melamine to form a C=N bond to obtain an intermediate 1, and then the intermediate 1 and DOPO react, and the C=N bond on the intermediate 1 reacts with the PH bond on the DOPO to obtain a fire-resistant enhancer; the molecular structure of the fire-resistant enhancer contains boron, nitrogen and phosphorus elements, so that it has the flame retardant effects of boron flame retardants, nitrogen flame retardants and phosphorus flame retardants at the same time, and the flame retardant performance is enhanced under the synergistic effect of the three, giving it excellent flame retardant performance. Therefore, adding the fire-resistant enhancer to the cable can effectively improve the fire resistance of the cable;
[0033] In the process of preparing tensile fire-resistant insulated cables, a reinforced glass fiber is also prepared. Phosphorus oxychloride and eugenol are reacted, and the chlorine atoms on the phosphorus oxychloride react with the chlorine atoms on the eugenol to introduce alkenyl groups to obtain intermediate 2. Then, meta-chloroperbenzoic acid is used as an oxidant to oxidize the alkenyl groups on intermediate 2 into epoxy groups to obtain intermediate 3. Then, intermediate 3 and silane coupling agent KH550 are reacted, and the epoxy groups on intermediate 3 react with the amino groups on the silane coupling agent KH550 to introduce a large number of siloxane groups to obtain a fiber modifier. Finally, the obtained fiber modifier is used to treat glass fiber. The glass fiber is modified, and the siloxane on the fiber modifier is hydrolyzed to form silanol, which can be grafted on the surface of the glass fiber, thereby improving its dispersibility and making it evenly compatible in the cable, greatly enhancing the mechanical properties of the cable and making it have excellent tensile properties. At the same time, the molecular structure of the fiber modifier contains phosphorus, nitrogen and a large amount of silicon, so that it has the flame retardant effects of phosphorus flame retardants, nitrogen flame retardants and silicon flame retardants at the same time. The synergistic effect of the three gives it excellent flame retardant properties. Therefore, adding reinforced glass fiber to the cable can further improve the fire resistance of the cable. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] This embodiment is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0037] Step S1: 30 mmol 4-formylphenylboronic acid, 10 mmol melamine and 40 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 20° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to 80° C. and stirred for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate 1;
[0038] Step S2: 10 mmol of intermediate 1, 30 mmol of DOPO and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 20° C. and a stirring rate of 300 r / min for 15 min, and then the mixture was heated to 80° C. and stirred for 8 h. After the reaction, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at 60° C. for 6 h to obtain a fire-resistant enhancer.
[0039] Step S3: 10 mmol phosphorus oxychloride, 33 mmol triethylamine and 50 mL ethyl acetate were added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and stirred for 30 min at a temperature of -5 ° C and a stirring rate of 300 r / min, and then 33 mL of eugenol was added dropwise while stirring. The eugenol solution formed by dissolving 10 mmol:10 mL eugenol in ethyl acetate was controlled at a dropping rate of 1 drop / s. After the dropwise addition was completed, the temperature was raised to 25 ° C and the stirring reaction was continued for 15 h. After the reaction was completed, the reaction product was added to ice water, and then allowed to stand for stratification. The organic phase was dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 2;
[0040] Step S4: 33 mmol of m-chloroperbenzoic acid and 70 mL of ethyl acetate were added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and the mixture was stirred for 30 min at a temperature of -5 ° C and a stirring rate of 300 r / min, and then 30 mL of the intermediate 2 solution formed by dissolving 10 mmol : 30 mL of the intermediate 2 in ethyl acetate was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the mixture was heated to 45 ° C and stirred for 15 h. After the reaction was completed, the reaction product was cooled to room temperature, and then washed twice with a saturated sodium bicarbonate solution, a saturated saline solution and distilled water in sequence, and then allowed to stand for stratification, and the organic phase was dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain the intermediate 3;
[0041] Step S5: 10 mmol of intermediate 3, 33 mmol of silane coupling agent KH550, 0.8 g of aluminum phosphotungstate and 80 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 20° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to 50° C. and stirred for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a fiber modifier;
[0042] Step S6: 10 g ECS 301T glass fiber, 1.2 g fiber modifier and 100 mL of 75% ethanol solution were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at 20 ° C. and a stirring rate of 300 r / min for 20 min, then heated to reflux and continued to stir for 8 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at 60 ° C. for 4 h to obtain reinforced glass fiber.
[0043] Step S7: weighing 56 parts of high-density polyethylene, 13 parts of polypropylene, 7 parts of fire-resistant reinforcing agent, 3 parts of reinforcing glass fiber, 4 parts of titanium dioxide, 3.5 parts of silicon powder, 1 part of calcium stearate, 0.9 parts of polyethylene wax, 0.5 parts of antioxidant 1010 and 0.3 parts of compatibilizer ABS-g-MAH according to weight parts;
[0044] Step S8: adding high-density polyethylene, polypropylene, fire-resistant reinforcing agent, reinforcing glass fiber, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing evenly to obtain a mixture;
[0045] Step S9: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0046] Embodiment 2:
[0047] This embodiment is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0048] Step S1: 30 mmol 4-formylphenylboronic acid, 10 mmol melamine and 45 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 22° C. and a stirring rate of 350 r / min for 25 min, and then the temperature was raised to 85° C. and stirred for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate 1;
[0049] Step S2: 10 mmol of intermediate 1, 30 mmol of DOPO and 55 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 22° C. and a stirring rate of 350 r / min for 18 min, and then the mixture was heated to 85° C. and continued to stir for 9 h. After the reaction, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at 62° C. for 7 h to obtain a fire-resistant enhancer.
[0050] Step S3: 10 mmol phosphorus oxychloride, 34 mmol triethylamine and 55 mL ethyl acetate were added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and stirred for 35 min at a temperature of -3 ° C and a stirring rate of 350 r / min, and then 34 mL of eugenol was added dropwise while stirring. The eugenol solution formed by dissolving 10 mmol:10 mL eugenol in ethyl acetate was controlled at a dropping rate of 1 drop / s. After the dropwise addition was completed, the temperature was raised to 28 ° C and the stirring reaction was continued for 18 h. After the reaction was completed, the reaction product was added to ice water, and then allowed to stand for stratification. The organic phase was dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain intermediate 2;
[0051] Step S4: 35 mmol m-chloroperbenzoic acid and 75 mL ethyl acetate are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and the mixture is stirred for reaction for 35 min at a temperature of -3°C and a stirring rate of 350 r / min, and then 30 mL of the intermediate 2 solution formed by dissolving 10 mmol:30 mL of the intermediate 2 in ethyl acetate is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the mixture is heated to 48°C and the stirring reaction is continued for 18 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed twice with a saturated sodium bicarbonate solution, a saturated saline solution and distilled water in sequence, and then allowed to stand for stratification, and the organic phase is dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain an intermediate 3;
[0052] Step S5: 10 mmol of intermediate 3, 35 mmol of silane coupling agent KH550, 1.2 g of aluminum phosphotungstate and 90 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 22° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was stirred at 52° C. for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a fiber modifier;
[0053] Step S6: 10 g ECS 301T glass fiber, 3.5 g fiber modifier and 110 mL of 80% ethanol solution were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 22 ° C and a stirring rate of 350 r / min for 25 min, then the temperature was raised to reflux and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature and then vacuum filtered. The filter cake was washed with anhydrous ethanol 4 times, and then placed in a vacuum drying oven and dried at a temperature of 62 ° C for 4.5 h to obtain reinforced glass fiber.
[0054] Step S7: weighing 62 parts of high-density polyethylene, 16 parts of polypropylene, 11 parts of fire-resistant reinforcing agent, 7 parts of reinforcing glass fiber, 6 parts of titanium dioxide, 5 parts of silicon powder, 2 parts of calcium stearate, 1.2 parts of polyethylene wax, 0.8 parts of antioxidant 1010 and 0.5 parts of compatibilizer ABS-g-MAH according to weight parts;
[0055] Step S8: adding high-density polyethylene, polypropylene, fire-resistant reinforcing agent, reinforcing glass fiber, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing evenly to obtain a mixture;
[0056] Step S9: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0057] Embodiment 3:
[0058] This embodiment is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0059] Step S1: 30 mmol 4-formylphenylboronic acid, 10 mmol melamine and 50 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to 90° C. and the mixture was stirred for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate 1;
[0060] Step S2: 10 mmol of intermediate 1, 30 mmol of DOPO and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 20 min, and then the mixture was heated to 90° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at 65° C. for 8 h to obtain a fire-resistant enhancer.
[0061] Step S3: 10 mmol phosphorus oxychloride, 35 mmol triethylamine and 60 mL ethyl acetate were added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and stirred for 40 min at a temperature of 0°C and a stirring rate of 400 r / min, and then 35 mL of eugenol was added dropwise while stirring. The eugenol solution formed by dissolving 10 mmol:10 mL eugenol in ethyl acetate was controlled at a dropping rate of 2 drops / s. After the addition was completed, the temperature was raised to 30°C and the stirring reaction was continued for 20 h. After the reaction was completed, the reaction product was added to ice water, and then allowed to stand for stratification. The organic phase was dried over anhydrous magnesium sulfate, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain intermediate 2;
[0062] Step S4: 36 mmol m-chloroperbenzoic acid and 80 mL ethyl acetate were added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and the mixture was stirred for 40 min at a temperature of 0°C and a stirring rate of 400 r / min, and then 30 mL of the intermediate 2 solution formed by dissolving 10 mmol:30 mL of the intermediate 2 in ethyl acetate was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the mixture was heated to 50°C and stirred for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then washed with saturated sodium bicarbonate solution, saturated brine and distilled water for 3 times in sequence, and then allowed to stand for stratification. The organic phase was dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain the intermediate 3;
[0063] Step S5: 10 mmol of intermediate 3, 36 mmol of silane coupling agent KH550, 1.6 g of aluminum phosphotungstate and 100 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 25° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was stirred at 55° C. for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a fiber modifier;
[0064] Step S6: 10 g ECS 301T glass fiber, 5.8 g fiber modifier and 120 mL of ethanol solution with a volume fraction of 85% were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 30 min, then the temperature was raised to reflux and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 5 h to obtain reinforced glass fiber.
[0065] Step S7: weighing 68 parts of high-density polyethylene, 19 parts of polypropylene, 15 parts of fire-resistant reinforcing agent, 11 parts of reinforcing glass fiber, 8 parts of titanium dioxide, 6.5 parts of silicon powder, 3 parts of calcium stearate, 1.5 parts of polyethylene wax, 10101.1 parts of antioxidant and 0.7 parts of compatibilizer ABS-g-MAH according to weight parts;
[0066] Step S8: adding high-density polyethylene, polypropylene, fire-resistant reinforcing agent, reinforcing glass fiber, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing evenly to obtain a mixture;
[0067] Step S9: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0068] Comparative Example 1:
[0069] This comparative example is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0070] Step S1: weigh 68 parts of high-density polyethylene, 19 parts of polypropylene, 8 parts of titanium dioxide, 6.5 parts of silicon powder, 3 parts of calcium stearate, 1.5 parts of polyethylene wax, 10101.1 parts of antioxidant and 0.7 parts of compatibilizer ABS-g-MAH according to weight parts;
[0071] Step S2: adding high-density polyethylene, polypropylene, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing evenly to obtain a mixture;
[0072] Step S3: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0073] Comparative Example 2:
[0074] This comparative example is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0075] Step S1: 30 mmol 4-formylphenylboronic acid, 10 mmol melamine and 50 mL anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to 90° C. and the mixture was stirred for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate 1;
[0076] Step S2: 10 mmol of intermediate 1, 30 mmol of DOPO and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 20 min, and then the mixture was heated to 90° C. and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at 65° C. for 8 h to obtain a fire-resistant enhancer.
[0077] Step S3: weighing 68 parts of high-density polyethylene, 19 parts of polypropylene, 15 parts of fire-resistant enhancer, 8 parts of titanium dioxide, 6.5 parts of silicon powder, 3 parts of calcium stearate, 1.5 parts of polyethylene wax, 10101.1 parts of antioxidant and 0.7 parts of compatibilizer ABS-g-MAH according to weight parts;
[0078] Step S4: adding high-density polyethylene, polypropylene, fire-resistant reinforcing agent, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing evenly to obtain a mixture;
[0079] Step S5: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0080] Comparative Example 3:
[0081] This comparative example is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0082] Step S1: 10 mmol phosphorus oxychloride, 35 mmol triethylamine and 60 mL ethyl acetate are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and stirred for 40 min at a temperature of 0°C and a stirring rate of 400 r / min, and then 35 mL of eugenol is added dropwise while stirring. The eugenol solution formed by dissolving 10 mmol:10 mL eugenol in ethyl acetate is added dropwise, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the temperature is raised to 30°C and the stirring reaction is continued for 20 h. After the reaction is completed, the reaction product is added to ice water, and then allowed to stand for stratification. The organic phase is dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain intermediate 2;
[0083] Step S2: 36 mmol m-chloroperbenzoic acid and 80 mL ethyl acetate are added to a three-necked flask equipped with a thermometer, a stirrer and a constant pressure dropping funnel, and the mixture is stirred for reaction for 40 min at a temperature of 0° C. and a stirring rate of 400 r / min, and then 30 mL of the intermediate 2 solution formed by dissolving 10 mmol : 30 mL of the intermediate 2 in ethyl acetate is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the mixture is heated to 50° C. and the stirring reaction is continued for 20 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with saturated sodium bicarbonate solution, saturated brine and distilled water for 3 times in sequence, and then allowed to stand for stratification, and the organic phase is dried over anhydrous magnesium sulfate, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain intermediate 3;
[0084] Step S3: 10 mmol of intermediate 3, 36 mmol of silane coupling agent KH550, 1.6 g of aluminum phosphotungstate and 100 mL of anhydrous acetone were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was stirred at 55° C. for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain a fiber modifier;
[0085] Step S4: 10 g ECS 301T glass fiber, 5.8 g fiber modifier and 120 mL of ethanol solution with a volume fraction of 85% were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred for reaction at a temperature of 25 ° C and a stirring rate of 400 r / min for 30 min, then the mixture was heated to reflux and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 65 ° C for 5 h to obtain reinforced glass fiber.
[0086] Step S5: weighing 68 parts of high-density polyethylene, 19 parts of polypropylene, 11 parts of reinforced glass fiber, 8 parts of titanium dioxide, 6.5 parts of silicon powder, 3 parts of calcium stearate, 1.5 parts of polyethylene wax, 10101.1 parts of antioxidant and 0.7 parts of compatibilizer ABS-g-MAH according to weight parts;
[0087] Step S6: adding high-density polyethylene, polypropylene, reinforced glass fiber, titanium dioxide, silica powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing evenly to obtain a mixture;
[0088] Step S7: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0089] Comparative Example 4:
[0090] This comparative example is a preparation process of a tensile fire-resistant insulated cable, comprising the following steps:
[0091] Step S1: weigh 68 parts of high-density polyethylene, 19 parts of polypropylene, 15 parts of DOPO, 11 parts of ECS 301T glass fiber, 8 parts of titanium dioxide, 6.5 parts of silica powder, 3 parts of calcium stearate, 1.5 parts of polyethylene wax, 1.1 parts of antioxidant 1010 and 0.7 parts of compatibilizer ABS-g-MAH according to weight parts;
[0092] Step S2: adding high-density polyethylene, polypropylene, DOPO, ECS 301T glass fiber, titanium dioxide, silica powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mixing them evenly to obtain a mixture;
[0093] Step S3: adding the mixture into an extruder, melting and extruding it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket, thereby obtaining a tensile-resistant and fire-resistant insulating cable.
[0094] The tensile-resistant fire-resistant insulation jackets of the tensile-resistant fire-resistant insulation cables in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, and the test results are as follows:
[0095]
[0096] Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that adding a fire-resistant reinforcing agent can significantly improve the flame retardant and fire-resistant properties of the cable, and adding reinforced glass fiber can significantly improve the tensile properties of the cable, and can further improve its flame retardant and fire-resistant properties. Therefore, under the synergistic effect of the fire-resistant reinforcing agent and the reinforced glass fiber, the prepared cable has excellent tensile and fire-resistant properties.
[0097] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0098] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A tensile fire-resistant insulated cable, characterized in that: It includes a copper wire core and a tensile-resistant fire-resistant insulating jacket outside the copper wire core; Wherein, the tensile fire-resistant insulating jacket comprises the following components in parts by weight: 56-68 parts of high-density polyethylene, 13-19 parts of polypropylene, 7-15 parts of fire-resistant reinforcing agent, 3-11 parts of reinforcing glass fiber, 4-8 parts of titanium dioxide, 3.5-6.5 parts of silicon powder, 1-3 parts of calcium stearate, 0.9-1.5 parts of polyethylene wax, 0.5-1.1 parts of antioxidant 1010 and 0.3-0.7 parts of compatibilizer ABS-g-MAH; Wherein, the fire-resistant reinforcing agent is prepared by the following steps: Step a1: stirring 4-formylphenylboronic acid, melamine and anhydrous ethanol for reaction, cooling the reaction product after the reaction is completed, and then rotary evaporating to obtain intermediate 1; Step a2: stirring the intermediate 1, DOPO and anhydrous ethanol for reaction, cooling the reaction product after the reaction is completed, then rotary evaporating, and then drying to obtain a fire-resistant enhancer; Wherein, the reinforced glass fiber is prepared by the following steps: Step b1: Phosphorus oxychloride, triethylamine and ethyl acetate are stirred for reaction, and then eugenol solution is added dropwise while stirring. After the addition is completed, the stirring reaction is continued. After the reaction is completed, the reaction product is added into ice water, and then allowed to stand for stratification. The organic phase is dried, and then vacuum filtered, and the filtrate is rotary evaporated to obtain intermediate 2; Step b2: stirring meta-chloroperbenzoic acid and ethyl acetate for reaction, then adding the intermediate 2 solution dropwise while stirring, continuing to stir the reaction after the addition is complete, cooling the reaction product after the reaction is complete, then washing, then standing to separate, drying the organic phase, then vacuum filtering, and rotary evaporating the filtrate to obtain intermediate 3; Step b3: stirring the intermediate 3, the silane coupling agent KH550, aluminum phosphotungstate and anhydrous acetone for reaction, cooling the reaction product after the reaction is completed, and then rotary evaporating to obtain a fiber modifier; Step b4: stirring the glass fiber, the fiber modifier and the ethanol solution to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain reinforced glass fiber.
2. A tensile fire-resistant insulated cable according to claim 1, characterized in that: The usage ratio of the 4-formylphenylboronic acid, melamine and anhydrous ethanol in step a1 is 30mmol:10mmol:40-50mL.
3. A tensile fire-resistant insulated cable according to claim 1, characterized in that: The usage ratio of the intermediate 1, DOPO and anhydrous ethanol in step a2 is 10 mmol: 30 mmol: 50-60 mL.
4. A tensile fire-resistant insulated cable according to claim 1, characterized in that: The phosphorus oxychloride, triethylamine, ethyl acetate and eugenol solution in step b1 are used in a ratio of 10 mmol:33-35 mmol:50-60 mL:33-35 mL; the eugenol solution is a solution formed by dissolving eugenol in ethyl acetate at a ratio of 10 mmol:10 mL.
5. A tensile fire-resistant insulated cable according to claim 1, characterized in that: The amount ratio of the meta-chloroperbenzoic acid, ethyl acetate and intermediate 2 solution in step b2 is 33-36mmol:70-80mL:30mL; the intermediate 2 solution is a solution formed by dissolving intermediate 2 in ethyl acetate at a ratio of 10mmol:30mL.
6. A tensile fire-resistant insulated cable according to claim 1, characterized in that: The usage ratio of the intermediate 3, silane coupling agent KH550, aluminum phosphotungstate and anhydrous acetone in step b3 is 10 mmol: 33-36 mmol: 0.8-1.6 g: 80-100 mL.
7. A tensile fire-resistant insulated cable according to claim 1, characterized in that: The amount ratio of the glass fiber, fiber modifier and ethanol solution in step b4 is 10g:1.2-5.8g:100-120mL; the glass fiber is ECS301T glass fiber, and the volume fraction of the ethanol solution is 75-85%.
8. A process for preparing a tensile fire-resistant insulated cable according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Weigh 56-68 parts of high-density polyethylene, 13-19 parts of polypropylene, 7-15 parts of fire-resistant reinforcing agent, 3-11 parts of reinforcing glass fiber, 4-8 parts of titanium dioxide, 3.5-6.5 parts of silicon powder, 1-3 parts of calcium stearate, 0.9-1.5 parts of polyethylene wax, 0.5-1.1 parts of antioxidant 1010 and 0.3-0.7 parts of compatibilizer ABS-g-MAH according to weight parts; Step 2: Add high-density polyethylene, polypropylene, fire-resistant reinforcing agent, reinforcing glass fiber, titanium dioxide, silicon powder, calcium stearate, polyethylene wax, antioxidant 1010 and compatibilizer ABS-g-MAH into a mixer and mix evenly to obtain a mixture; Step 3: Add the mixture into the extruder, melt and extrude it onto the outside of the copper wire core to form a tensile-resistant and fire-resistant insulating jacket to obtain a tensile-resistant and fire-resistant insulating cable.
Citation Information
Patent Citations
Insulating and anticorrosive paint for high voltage cable
CN106634271A
High-strength cable material
CN108034165A
Cable material with high toughness and high temperature resistance
CN108641158A
Preparation method and application of flame retardant containing phosphorus, nitrogen and boron
CN111116661A